2022
DOI: 10.1007/s10973-022-11799-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of basalt fibre composites in thermal shielding

Abstract: This present study demonstrates the applicability of basalt fibre-reinforced polymer (BFRP) composite materials in thermal shielding. Basalt fibres are produced from natural, sustainable sources and obtain comparable mechanical performance to commercial glass fibres. In addition to their mechanical strength, BFRPs have excellent chemical and heat resistance. Basalt fibres tend to have a higher thermal stability than their competitor glass fibres. The heat resistance of basalt fibres derives from the volcanic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…23 Szegő is azt emeli ki, hogy a novellákban "kirajzolódnak a Rakovszky-(kis)epika leglényegesebb motívumai", illetve "a pszichológiai perspektíva és narratíva" meghatározó szerepéről ír, ami egyfajta "lélektani realizmus" felől teszi értelmezhetővé az elbeszéléseket. 24…”
Section: Kontextusunclassified
“…23 Szegő is azt emeli ki, hogy a novellákban "kirajzolódnak a Rakovszky-(kis)epika leglényegesebb motívumai", illetve "a pszichológiai perspektíva és narratíva" meghatározó szerepéről ír, ami egyfajta "lélektani realizmus" felől teszi értelmezhetővé az elbeszéléseket. 24…”
Section: Kontextusunclassified
“…Some studies have shown that TiO 2 could promote the formation of char layers, and both oxides of iron and SiO 2 have also been shown to promote the flame retardancy of materials. In addition, BF exhibits high strength, excellent thermal stability, and chemical stability. , Therefore, the production of inorganic paper using BFs holds a promising application in the fields of fire retardance and thermal insulation. However, as a result of its chemical inertness, it is necessary to introduce reinforcing phases in the BF network to improve paper-forming properties and provide more possibilities for the application of BFs in the field of paper-based materials. Aramid fiber is a high-performance organic synthetic fiber with lightweightness, good thermal stability, chemical resistance, insulation, and self-extinguishing properties. Aramid nanofibers (ANFs) retain these excellent properties of macroscopic aramid fibers . Previous studies have shown that ANFs can be used to prepare materials with excellent thermal stability and insulation through processes such as electrospinning, vacuum-assisted pumping filtration, and freeze drying. In addition, ANFs also own the characteristics of nanomaterials, such as high specific surface area and high aspect ratio, which help to improve the interfacial bonding with the substrate, thus enhancing the mechanical properties of the material. , ANFs can serve as reinforcing phases in composites with other matrices, such as bacterial cellulose, poly­(vinyl alcohol), hydroxyethyl cellulose, and carbon nanotubes, improving interface bonding and resulting in a significant enhancement of mechanical strength. Therefore, ANFs show great applications in various high-performance and multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, basalt fiber is an environmentally friendly option with a cost comparable to other fiber types. Moreover, it enhances temperature resistance, corrosion resistance, chemical properties, and mechanical properties (Karacor and Ozcanli, 2022;Shoaib et al, 2022;Tamás-Bényei and Sántha, 2023).…”
Section: Introductionmentioning
confidence: 99%